2008
DOI: 10.1099/vir.0.83517-0
|View full text |Cite
|
Sign up to set email alerts
|

Altered chemotactic response of myeloid and plasmacytoid dendritic cells from patients with chronic hepatitis C: role of alpha interferon

Abstract: Dendritic cell (DC) frequencies in the blood of patients with chronic hepatitis C virus (HCV) infection have been shown to be reduced significantly compared with those in healthy individuals. There is a further reduction of circulating myeloid DCs (MDCs) and plasmacytoid DCs (PDCs) in HCV patients receiving alpha interferon (IFN-a)-based antiviral therapy. Altered homing behaviour of DCs may be a possible mechanism for their 'loss' in peripheral blood in these clinical conditions. Systemic chemokine levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 55 publications
2
25
1
Order By: Relevance
“…Therefore, it is plausible that PDC may migrate from the liver to periphery/lymphoid tissue after being unleashed from chemokines in the liver. In support for this, it is reported that IFN-a alters the profiles of chemokine receptors on DC, resulting in changes of the DC migrating ability [34].…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it is plausible that PDC may migrate from the liver to periphery/lymphoid tissue after being unleashed from chemokines in the liver. In support for this, it is reported that IFN-a alters the profiles of chemokine receptors on DC, resulting in changes of the DC migrating ability [34].…”
Section: Discussionmentioning
confidence: 93%
“…31 No.7 are fully competent in inducing PDCs adhesion and migration when immobilized on heparan sulphates expressed by endothelial cells [33]. Two recent reports showed that PDCs purified from patients with chronic hepatitis C, or exposed in vitro to IFN-a, acquire the ability to respond to CCR2, CCR5 and CXCR3 ligands [44,45]. These results suggest that under appropriate stimulatory conditions, additional chemokine receptors may be involved in human PDCs recruitment.…”
Section: Reviewmentioning
confidence: 97%
“…However, when CXCR3 ligands were immobilized on heparan sulphates expressed by endothelial cells, they became totally competent to induce pDC migration [105]. In addition, pDCs purified from patients with chronic hepatitis C, or exposed in vitro to IFN-a, acquire the ability to respond to CCR2, CCR5 and CXCR3 ligands [106,107], suggesting that appropriate stimulatory conditions may increase the range of chemokines able to recruit pDCs to inflamed tissues. pDCs were also described to express functional receptors for adenosine [108], F2L [109] and for the complement anaphylatoxins C3a and C5a [110], and to migrate in response to IL-18 [111]; all these signals are released in inflamed tissues.…”
Section: Recruitment In Autoimmune Diseasesmentioning
confidence: 99%